Fluctuación poblacional de Quadrastichus mendeli, controlador biológico de la avispa de la agalla de los Eucaliptos Leptocybe invasa en el Norte de Misiones = Population fluctuation of Quadrastichus mendeli, biological controller of the Eucalyptus gall wasp Leptocybe invasa in north of Misiones - Eskiviski, Edgar Rafael (2023)
The objective of this study was to determine the population fluctuation of the parasitoid Quadrastichus mendeli and its host, Leptocybe invasa in Misiones. Two Eucalyptus grandis plantations where evaluated. In field, yellow sticky traps were placed and in the laboratory, the identification and counting of the captured insects was carried out. Q. mendeli was determined at higher population levels than its host. The population peak occurred during the late autumn during the month of May. It is considered that Q. mendeli is established in the region and at population levels that contribute positively to integrated pest management